1997
DOI: 10.2500/108854197778594089
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Nasal Eosinophilia in Allergy Clinic Patients as Determined by Swab and Curette Sampling

Abstract: The presence of eosinophils in nasal secretions often characterizes inflammatory disease in the nose and paranasal sinuses. This study analyzed differential associations between various clinical parameters and the presence of nasal eosinophilia in mucosal specimens obtained by two sampling methods (swab and curette-probe). Nasal mucosal secretions were obtained in patients attending an adult allergy clinic using both sampling methods for each patient. The presence of eosinophilia as determined by both methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
5
2
Order By: Relevance
“…Our results are not directly comparable with previous ones, as the only one study assessing diagnostic accuracy of NSW compared to NSC only focused on the identification of the eosinophilic pattern in allergic adults (20) and did not evaluate the tolerability of the tools. However, our data is in line with results by Lin et al (20) , which showed that the curette-probe determined…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are not directly comparable with previous ones, as the only one study assessing diagnostic accuracy of NSW compared to NSC only focused on the identification of the eosinophilic pattern in allergic adults (20) and did not evaluate the tolerability of the tools. However, our data is in line with results by Lin et al (20) , which showed that the curette-probe determined…”
Section: Discussioncontrasting
confidence: 99%
“…proposed (including blowing the nose, nasal brushing, and direct biopsy) (4,(13)(14)(15) , NSC still represents the tool of choice (18,19) given that it was found to be more accurate than both cotton swab and brushing in adult population (20) and it is supposed to be well tolerated by the paediatric population, too. However, we have to take into account that NSC is not a nasal biopsy and as such could perhaps over or underestimate nasal pathology.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge this is the first study evaluating diagnostic accuracy of NSW in assessing nasal cytotypes in children. NSC was chosen as the comparing sampling technique because even if different sampling methods have been proposed (including blowing the nose, nasal brushing, and direct biopsy) (4,(13)(14)(15) , NSC still represents the tool of choice (18,19) given that it was found to be more accurate than both cotton swab and brushing in adult population (20) and it is supposed to be well tolerated by the paediatric population, too. However, we have to take into account that NSC is not a nasal biopsy and as such could perhaps over or underestimate nasal pathology.…”
Section: Discussionmentioning
confidence: 99%
“…During each appointment, subjects completed an UPSIT and underwent nasal cell collection with 2 comfortable methods, the nasal curette (Arlington Scientific, Springville, UT) and cytobrush (Erskine Dental, Marina Del Ray, CA). Both are established methods used to collect nasal specimens for cytologic studies . At follow‐up, subjects also completed a subjective transition scale regarding their smell function.…”
Section: Methodsmentioning
confidence: 99%